2015
DOI: 10.1071/sh13131
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s perceptions of sexual and reproductive health in regional and rural Queensland: capturing the views of adolescents through reference groups and a user-friendly electronic survey

Abstract: Service provision can be improved by training, and retaining friendly, attentive and non-judgemental staff. A model of service provision that includes general health care and provides sexual health services may increase the acceptability and accessibility of SRH services among youth. Additionally, our study highlights the need for choice between general and specialist SRH services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…30 Likewise, in this study, service providers recognised the negative impact of stigma, shame and embarrassment on health care-seeking behaviour. 23 Such networks may present the best way of promoting the 'friendliness' of a service. Young people themselves highlighted the influence of interpersonal factors by rating the attitudes of service providers as the most important marker of quality in a service.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Likewise, in this study, service providers recognised the negative impact of stigma, shame and embarrassment on health care-seeking behaviour. 23 Such networks may present the best way of promoting the 'friendliness' of a service. Young people themselves highlighted the influence of interpersonal factors by rating the attitudes of service providers as the most important marker of quality in a service.…”
Section: Discussionmentioning
confidence: 99%
“…23 Responses from young people between the ages of 15 years old (yo) and 24yo were gathered through peerfacilitated survey administration on tablet devices (iPads; Apple Inc., Cupertino, California, USA) at community events, university events, Family Planning Queensland clinics and shopping centres. The survey aimed to capture both young people utilising health services for SRH issues and those who have not accessed such services.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Mazza and colleagues found that the rate of management of contraceptive problems was lower for Indigenous women attending for primary care than for non‐Indigenous women (4.48% v 6.15% of consultations), and that their contraceptive problems were much less frequently managed by male doctors 6 . The reality for people living in rural and remote Australia is that their access to services taken for granted by urban residents is limited, as is their choice of provider 7 . In terms of SRH, this is particularly apparent in terms of access to termination of pregnancy, tubal ligation, and insertion of intra‐uterine devices, where the limiting factor is often the lack of appropriately trained staff or of culturally acceptable services.…”
mentioning
confidence: 99%